A cost-effectiveness analysis of two different antimicrobial stewardship programs - Okumura,Lucas Miyake (2016)
Abstract There is a lack of formal economic analysis to assess the efficiency of antimicrobial stewardship programs. Herein, we conducted a cost-effectiveness study to assess two different strategies of Antimicrobial Stewardship Programs. A 30-day Markov model was developed to analyze how cost-effective was a Bundled Antimicrobial Stewardship implemented in a university hospital in Brazil. Clinical data derived from a historical cohort that compared two different strategies of antimicrobial stewardship programs and had 30-day mortality as main outcome. Selected costs included: workload, cost of defined daily doses, length of stay, laboratory and imaging resources used to diagnose infections. Data were analyzed by deterministic and probabilistic sensitivity analysis to assess model's robustness, tornado diagram and Cost-Effectiveness Acceptability Curve. Bundled Strategy was more expensive (Cost difference US$ 2119.70), however, it was more efficient (US$ 27,549.15 vs 29,011.46). Deterministic and probabilistic sensitivity analysis suggested that critical variables did not alter final Incremental Cost-Effectiveness Ratio. Bundled Strategy had higher probabilities of being cost-effective, which was endorsed by cost-effectiveness acceptability curve. As health systems claim for efficient technologies, this study conclude that Bundled Antimicrobial Stewardship Program was more cost-effective, which means that stewardship strategies with such characteristics would be of special interest in a societal and clinical perspective.